Edukasi Tools Artificial Intelligences dalam Meningkatkan Kemampuan Dosen untuk Menyusun Artikel Sinta dan Scopus - Shantilawati, Irma; Yusron, Ali; Andas, Netty Huzniati; Sumiarti, Sumiarti; Rahmah, St. (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to improve lecturers' competency in writing reputable scientific articles indexed by SINTA and Scopus through optimizing the use of artificial intelligence (AI) tools. The PKM implementation method uses a participatory training approach that includes material presentation sessions, hands-on practice using various AI applications such as literature review tools, paraphrasing tools, and proofreading assistants, and intensive mentoring in the article drafting process. The results of this activity showed a significant increase in the understanding and technical skills of the participating lecturers. Before the training, the majority of participants admitted to having difficulty conducting comprehensive literature research, improving academic grammar, and ensuring manuscripts comply with international standards. After participating in the series of activities, the lecturers were not only able to operate various AI tools independently but also successfully completed initial drafts of their articles with better structure and more standardized language quality. The output of this activity is increased lecturer productivity in producing scientific articles ready for submission to accredited national journals and reputable international journals.